Removable Partial Denture Components and Applications: A Team-Based Learning Module - Luisa Echeto (Association of American Medical Colleges, 2016)
Abstract Introduction The process of learning the removable partial denture (RPD) requires that students first acquire fundamental concepts and then use critical thinking skills to apply that knowledge to different clinical scenarios. We believed this course posed a perfect opportunity to transition to an active learning method, namely team-based learning (TBL). Methods In each TBL session the instructor creates adequate teams and assigns reading materials to the students in preparation for the readiness assurance process. While in class, individual students complete a case-based, multiple-choice examination to ensure their readiness to apply their foundational knowledge. Once all individual members of each team complete their individual tests, they retake the same examination as a team. During this process, they must reach consensus on their answers, which promotes discussion, debate, and learning. This module also presents an application assignment. Every team is presented with the same significant problem, is asked to come up with a specific answer, and reports simultaneously with the other teams, which results in a productive and vigorous debate. Results The shift to the TBL format resulted in a lower quantitative overall course evaluation compared to prior years, yet paradoxically, students' comments reflected a change in their attitudes and knowledge gain. From an administrative perspective, the shift added substantial value since there were 2 fewer hours of student class contact time and 98 fewer hours of faculty time assigned to the course. Discussion The RPD course transition to active learning was supported by our College Curriculum Committee goals. Placing the responsibility for learning on the student enhances his/her learning ability and allows time for instructors to teach at another level.